Oxford handbook of head and neck anatomy - Gijn, Daniel R. van; Newlands, Carrie; Roberts, Alice; Dunne, Jonathan; Standring, Susan; Eccles, Simon (Oxford, United Kingdom : Oxford University Press, 2022)
The Oxford Handbook of Head and Neck Anatomy will cover the clinically applied, complex anatomy of the head and neck in a practical, user-friendly and succinct format. Written and illustrated by subject experts, it provides an authoritative quick reference.
Description based upon print version of record.
WorldCat record variable field(s) change: 650
Keywords: Head -- Anatomy; Neck -- Anatomy